Melon2K array: A versatile 2K liquid SNP chip for melon genetics and breeding - Qing Yu; Shuai Li; Xiaofeng Su; Xinxiu Chen; Yuanhua Dong; Zhiwang Yao; Naiyu Jiang; Sen Chai; Zhonghua Zhang; Kuipeng Xu (Horticultural Plant Journal)
High-throughput genotyping tools can effectively promote molecular breeding in crops. In this study, genotyping by target sequencing (GBTS) system was utilized to develop a genome-wide liquid SNP chip for facilitating genetics and breeding in melon (Cucumis melo L.), a globally cultivated economically important horticultural crop. Based on over eight million SNPs derived from 823 representative melon accessions, 16K, 8K, 4K, 2K, 1K, 500, 250 and 125 informative SNPs were screened and evaluated for their polymorphisms, conservation of flanking sequences, and distributions. The set of 2K SNPs was found to be optimal for representing the maximum diversity with the lowest number of SNPs, and it was selected to develop the liquid chip, named “Melon2K”. Using Melon2K, more than 1500 SNPs were detected across 17 samples of five melon cultivars, and the phylogenetic relationships were clearly constructed. Within the same cultivar, genetic differences were also assessed between different samples. We evaluated the performance of Melon2K in genetic background selection during the breeding process, obtaining the introgression lines of interested trait with more than 97% genetic background of elite variety by only two rounds of backcrossing. These results suggest that Melon2K provides a cost-effective, efficient and reliable platform for genetic analysis and molecular breeding in melon.